2018
DOI: 10.1109/jtehm.2018.2870589
|View full text |Cite
|
Sign up to set email alerts
|

Passive Self Resonant Skin Patch Sensor to Monitor Cardiac Intraventricular Stroke Volume Using Electromagnetic Properties of Blood

Abstract: This paper focuses on the development of a passive, lightweight skin patch sensor that can measure fluid volume changes in the heart in a non-invasive, point-of-care setting. The wearable sensor is an electromagnetic, self-resonant sensor configured into a specific pattern to formulate its three passive elements (resistance, capacitance, and inductance). In an animal model, a bladder was inserted into the left ventricle (LV) of a bovine heart, and fluid was injected using a syringe to simulate stoke volume (SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Electromagnetic induction measurement has high application prospects in bedside and point-of-care monitoring. Recently, Alruwailli et al showed that resonant skin patch sensors can be used to detect changes in the cardiac intraventricular stroke volume, thereby providing a non-invasive monitoring index for stroke patients [ 57 ]. Mohammed et al proposed a wearable readout system to carry out hemodynamic detection by extracting the radio frequency attributes of resonant frequency shift and magnitude variation [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electromagnetic induction measurement has high application prospects in bedside and point-of-care monitoring. Recently, Alruwailli et al showed that resonant skin patch sensors can be used to detect changes in the cardiac intraventricular stroke volume, thereby providing a non-invasive monitoring index for stroke patients [ 57 ]. Mohammed et al proposed a wearable readout system to carry out hemodynamic detection by extracting the radio frequency attributes of resonant frequency shift and magnitude variation [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin patch sensors based on electromagnetic (EM) detection were built from a conductive trace of copper to measure intravascular stroke volume [124] and intracranial blood pressure [158]. Also, a magnetoelastic skin curvature sensor along with ECG electrodes was used to measure blood pressure in the carotid [159].…”
Section: Transducing Modalities and Materials For Non-invasive Blood mentioning
confidence: 99%
“…In the stroke volume method, mean arterial blood pressure is estimated through measuring changes in the volume of blood pumped from the left ventricle (i.e., cardiac output) and the resistance that must be overcome to push blood and create flow in arteries (i.e., systemic vascular resistance) or through estimating cardiac output from O 2 consumption levels [ 123 ]. The accuracy of the contact [ 124 , 125 ] and non-contact [ 126 , 127 , 128 ] sensing modalities of the blood flow method is controversial. Contact sensing has met the gold standard level of accuracy under certain conditions and failed to meet it under others, whereas non-contact sensing modalities show a significant reduction in diagnostic performance [ 127 , 128 ].…”
Section: Blood Pressure Measurementmentioning
confidence: 99%
“…Also, the feasibility of using the fat channel for intra-body communication at microwave frequencies has been studied [ 25 ]. In vivo characterization using microwave sensors have been done in hip fracture healing [ 26 ], to monitor intracranial pressure [ 27 ], measure fluid volume changes in the heart [ 28 ] and measure limb hemodynamics [ 29 ]. Recently, non-invasive techniques to characterize the dielectric properties and analyze variations in biological tissues are being studied for their potential to determine muscle mass and quality [ 30 ].…”
Section: Introductionmentioning
confidence: 99%